Effect of Fragmentation on Pore Structures and Fractal Characteristics of Intact Coal and Deformed Coal Based on Experiments - Mingjie Li; Shouqing Lu; Chengfeng Wang; Jie Liu; Jiang Shi; Taibiao Bei (Geofluids)
Coal mining has to develop to deeper strata with the increasing demand for coal, which leads to frequent coal and gas outburst disasters. Especially, when there is a deformed coal in the coal seam, the outburst disasters are easier and more intense. Coal and gas outburst disasters can be promoted by the fragmentation. In order to clearly explain the reasons for the impact of fragmentation on deformed coal and gas outburst, mercury intrusion porosimetry, low-temperature liquid N2 adsorption test, and scanning electron microscope were carried out in this paper. The differences in pore characteristics of intact coal and deformed coal under different particle size conditions were analyzed from pore shapes, pore size distributions, and fractal dimensions. The damage paths of fragmentation on various kinds of pores in intact coal are as follows: macropores, mesopores, minipores, and micropores, and those on various kinds of pores in deformed coal are as follows: macropores, micropores, mesopores, and minipores. According to the fractal dimension theory and experimental results, the calculative results of fractal dimensions show that the fragmentation and tectonism reduce the surface roughness and structural complexity of macropores and mesopores and increase those of minipores and micropores in deformed coal. Finally, combined with the coupling effect of fragmentation and tectonism on pores, the reason of deformed coal with high crushing degree in fields of outburst was explained. The research provides the basis for the prevention of coal and gas outburst.